Proficient Language Learners’ Perception on the Use of Affective Strategies in Presentation - Tania Tahmina (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
EFL learners employ various strategies in presentation. Affective strategies help them to give effective presentation in English on any topic. The objective of this study was to find out the most frequently used affective strategies adopted by the proficient learners of the Department of English, Jagannath University, Dhaka, Bangladesh, in their presentation sessions. A mixed-methods approach was used to collect the data in this research. The participants of this research were fourteen (five males and nine females) proficient learners. Oxford’s (1990) SILL (“Strategy Inventory for Language Learning”) questionnaire and interview were used to collect the data. The result showed that the good language learners employed the following affective strategy most frequently to develop their presentation skills: “I encourage myself to speak a foreign language even when I am afraid of making a mistake” (50% ). The next most frequently used strategy was “I talk to someone else about how I feel when I am learning a foreign language” (42.85% ). The third most used strategy was “I notice if I am tensed or nervous when I am studying or using a foreign language” (28.59%). The findings of the research will help learners to develop their presentation skills in English in Bangladesh.